2021
DOI: 10.1177/09612033211025614
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between irreversible organ damage and the quality of life of patients with systemic lupus erythematosus: The Kyoto Lupus Cohort survey

Abstract: Objectives It is important to clarify the relationship between irreversible organ damage and the quality of life (QOL) by considering the unique factors of patients with systemic lupus erythematosus (SLE). We aimed to clarify their correlation using SLE-specific QOL assessment tools. We also aimed to identify which type of organ damage is adversely correlated with the QOL. Methods We conducted a questionnaire-based survey of outpatients with SLE at Kyoto University Hospital and evaluated irreversible organ dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Irreversible damage (as assessed by Systemic Lupus International Collaborating Clinics [SLICC] score/ American College of Rheumatology [ACR] damage index) is widely recognized to be associated with poorer quality of life, with the type of organ involvement potentially affecting disability and work ability differently [ 45 , 46 ]. For example, a past study found that organ damage, specifically musculoskeletal damage, was negatively correlated with HRQoL, particularly the physical and social aspects [ 46 ]. A second study reported similar findings, with skin and joint involvement leading to a higher proportion of the patients experiencing activity impairment [ 45 ], indicating that patients with this type of organ damage should be examined and monitored closely in clinical practice [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Irreversible damage (as assessed by Systemic Lupus International Collaborating Clinics [SLICC] score/ American College of Rheumatology [ACR] damage index) is widely recognized to be associated with poorer quality of life, with the type of organ involvement potentially affecting disability and work ability differently [ 45 , 46 ]. For example, a past study found that organ damage, specifically musculoskeletal damage, was negatively correlated with HRQoL, particularly the physical and social aspects [ 46 ]. A second study reported similar findings, with skin and joint involvement leading to a higher proportion of the patients experiencing activity impairment [ 45 ], indicating that patients with this type of organ damage should be examined and monitored closely in clinical practice [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…[SLICC] score/ American College of Rheumatology [ACR] damage index) is widely recognized to be associated with poorer quality of life, with the type of organ involvement potentially affecting disability and work ability differently [45,46]. For example, a past study found that organ damage, specifically musculoskeletal damage, was negatively correlated with HRQoL, particularly the physical and social aspects [46].…”
Section: Irreversible Damage (As Assessed By Systemic Lupus Internati...mentioning
confidence: 99%
“…[SLICC] score/ American College of Rheumatology [ACR] damage index) is widely recognized to be associated with poorer quality of life, with the type of organ involvement potentially affecting disability and work ability differently [45,46]. For example, a past study found that organ damage, specifically musculoskeletal damage, was negatively correlated with HRQoL, particularly the physical and social aspects [46]. A second study reported similar findings, with skin and joint involvement leading to a higher proportion of the patients experiencing activity impairment [45], indicating that patients with this type of organ damage should be examined and monitored closely in clinical practice [46].…”
Section: Irreversible Damage (As Assessed By Systemic Lupus Internati...mentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease with great heterogeneity in its clinical course and treatment response. In addition to minimization of flares and optimizing health‐related quality of life, one of the major treatment goals in SLE is prevention of organ damage, as this predicts mortality and poorer quality of life 1,2 . The Systemic Lupus International Collaborating Clinic/American College of Rheumatology (ACR) Damage Index (SDI) is a validated instrument that measures organ damage present for at least 6 months as a consequence of the disease itself or treatment 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to minimization of flares and optimizing health-related quality of life, one of the major treatment goals in SLE is prevention of organ damage, as this predicts mortality and poorer quality of life. 1,2 The Systemic Lupus International Collaborating Clinic/American College of Rheumatology (ACR) Damage Index (SDI) is a validated instrument that measures organ damage present for at least 6 months as a consequence of the disease itself or treatment. 3 SDI evaluates damage across 12 organ systems, and the total SDI score represents the burden of damage.…”
Section: Introductionmentioning
confidence: 99%